Oti axamiyagiri: Assamese nationalistic masculine identity, United Liberation Front of Asom and cyberspace. (April 2023) - Sarmah, Parikshit; Nath, Debarshi Prasad
This paper argues that the emergence of social media as a new public sphere has shaped masculine identity in the cyber platform. Such masculinity in Assamese society (the Assamese-speaking community), based on the images of the ideal Assamese man is linked with a form of Assamese nationalistic masculinity that gathered momentum during the Assam Movement (1979–1985). Politics of identity in Assam is basically trapped in the world of appearances, fighting real and imaginary enemies, and drawing strength from prejudices and misconceptions of groups, about themselves and others. This process of identity creation also shaped the identity of the "ideal" Assamese man in the recent socio-political history of Assam. This article is an attempt to define how masculinity works in the cyber world by focusing attention on Assamese nationalistic masculinity which is based on the image of the "RealAssamese Man." The "Real Assamese Man, " in turn, draws inspiration from a socio-cultural context which started with the creation of Assamese iconographies of masculinity which were later transformed and appropriated to serve the purpose of identity-politics.